PENGARUH SUBSTITUSI TEPUNG AZOLLA (Azolla microphylla) DALAM RANSUM TERHADAP TOTAL PROTEIN PLASMA DAN SEL DARAH MERAH BROILER JANTAN - Arif Kurniadi; Farida Fathul; Siswanto Siswanto; Madi Hartono (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
The study aimed to find out the best effect and dose of Azolla microphylla flour substitution in rations on total plasma proteins and red blood cells of male broiler. This research was conducted in March - April 2021 at PT. Sinar Ternak Sejahtera, South Lampung. Blood samples of this study were analyzed at Lampung Veterinary center, Bandar Lampung. The study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Treatment given was ration without substitution of Azolla flour (P0), rations with substitution of Azolla flour 2.5% (P1), rations with substitution of Azolla flour 5% (P2), and rations with substitution of Azolla flour 7.5% (P3). The data obtained were analyzed descriptively. The results of descriptive analysis showed that substitution of Azolla flour in rations had no effect on total plasma protein and red blood cells of male broilers which impacted on the health of broiler chickens. The average value of total plasma proteins obtained in each treatment group was 3.47 ± 0.12 g/ml; 3.60 ± 0.10 g/ml; 3.53 ± 0.23 g/ml; and 3.43 ± 0.15 g/ml for P0, P1, P2 and P3, respectively. The average value of red blood cells obtained in each treatment group was 3.51 ± 0.15 x 106/mm3; 2.94 ± 0.11 x 106/mm3; 3.74 ± 0.22 x 106/mm3; and 2.79 ± 0.15 x 106/mm3 for P0, P1, P2 and P3, respectively. Keywords: Azolla flour, Erythrocytes, Male broiler, Substitution, Total plasma protein